A Comprehensive Guide to Corpus Linguistics: A Book Review of Corpora in Applied Linguistics - ASTRI, Zul; NONI, Nurdin; HALIM, Abd; NOER, Fhadli (Politeknik Negeri Ujung Pandang, 2024)
Corpora have emerged as a transformative tool in the field of linguistics, providing researchers with a robust, data-driven approach to understanding language use. By compiling large collections of texts-ranging from written documents to transcriptions of spoken language-corpus linguistics enables the analysis of authentic language in its natural context. Corpora in applied linguistics have revolutionized the study of language by providing a data-driven approach to understanding linguistic phenomena. By analyzing large collections of naturally occurring texts, researchers can uncover patterns, frequencies, and contextual usages that are not easily identifiable through traditional methods. This approach has not only enhanced the theoretical foundations of linguistics but has also offered practical applications in fields such as language teaching, discourse analysis, and translation studies. As highlighted by Hunston (2002), McEnery and Hardie (2011), and Biber, Conrad, and Reppen (1998), the integration of corpus methodologies into linguistic research has not only deepened theoretical insights but also provided practical tools for educators and researchers alike. Susan Hunston's